Rapid donor T‐cell engraftment increases the risk of chronic graft‐versus‐host disease following salvage allogeneic peripheral blood hematopoietic cell transplantation for bone marrow failure syndromes. Issue 10 (3rd September 2013) - Pantin, Jeremy; Tian, Xin; Shah, Avni A.; Kurlander, Roger; Ramos, Catalina; Cook, Lisa; Khuu, Hahn; Stroncek, David; Leitman, Susan; Barrett, John; Donohue, Theresa; Young, Neal S.; et al.
<x xml:space="preserve">Abstract</x> The risk of graft‐rejection after allogeneic hematopoietic cell transplantation using conventional cyclophosphamide‐based conditioning is increased in patients with bone marrow failure syndromes (BMFS) who are heavily transfused and often HLA‐alloimmunized. Fifty‐six patients with BMFS underwent fludarabine‐based reduced‐intensity conditioning and allogeneic peripheral blood progenitor cell (PBPC) transplantation at a single institution. The conditioning regimen consisted of intravenous cyclophosphamide, fludarabine, and equine antithymocyte globulin. Graft‐versus‐host disease (GVHD) prophylaxis included cyclosporine A alone or in combination with either mycophenolate mofetil or methotrexate. To reduce the risk of graft‐rejection/failure, unmanipulated G‐CSF mobilized PBPCs obtained from an HLA‐identical or single HLA‐antigen mismatched relative were transplanted rather than donor bone marrow. Despite a high prevalence of pretransplant HLA‐alloimmunization (41%) and a heavy prior transfusion burden, graft‐failure did not occur with all patients having sustained donor lympho‐hematopoietic engraftment. The cumulative incidence of grade II–IV acute‐GVHD and chronic‐GVHD was 51.8% and 72%, respectively; with 87.1% surviving at a median follow‐up of 4.5 years. A multivariate analysis showed pretransplant alloimmunization and rapid donor T‐cell engraftment (≥95% donor by day 30) were both significantly (P < 0.05) associated with the development of chronic‐GVHD (adjusted HR 2.13 and 2.99, respectively). These data show fludarabine‐based PBPC transplantation overcomes the risk of graft‐failure in patients with BMFS, although rapid donor T‐cell engraftment associated with this approach appears to increase the risk of chronic‐GVHD. (Clinicaltrials.gov identifier: NCT00003838). Am. J. Hematol. 88:874–882, 2013. © 2013 Wiley Periodicals, Inc.